1 18F-fluoride and 18F-fluorodeoxyglucose positron emission tomography after transient ischaemic attack or minor ischaemic stroke. (May 2018) - Vesey, Alex T; Jenkins, William SA; Irkle, Agnese; Moss, Alastair; Sng, Greg; Forsythe, Rachael O; Clark, Tim; Roberts, Gemma; Fletcher, Alison; Lucatelli, Christophe; Rudd, James HF; Davenport, Anthony P; et al.
Abstract : Introduction: Combined positron emission tomography (PET) and computed tomography (CT) has the potential to assess both the anatomy and biology of carotid atherosclerosis. We sought to assess whether 18F-fluoride or 18F-fluorodeoxyglucose can identify culprit and high-risk carotid plaque. Methods: We performed 18F-fluoride and 18F-fluorodeoxygluose PET/CT in 26 patients following recent stroke/transient ischaemic attack: 18 patients with culprit carotid stenosis awaiting carotid endarterectomy and 8 control patients without culprit carotid atheroma. We compared standardised uptake values (SUVs) in the clinically adjudicated culprit to the contralateral asymptomatic artery, and assessed the relationship between radiotracer uptake and plaque phenotype or predicted cardiovascular risk. Results: Carotid 18F-fluoride uptake was increased in clinically adjudicated culprit plaques compared to the asymptomatic contralateral plaques (log10 SUVmean 0.29±0.10 versus 0.23±0.11, p=0.001) and compared to control patients (log10 SUVmean 0.29±0.10 versus 0.12±0.11, p=0.001). 18F-Fluoride uptake correlated with high-risk plaque features (remodelling index [r=0.53, p=0.003]; plaque burden [r=0.51, p=0.004]) and predicted cardiovascular risk (r=0.65, p=0.002). Consistent with the binding of necrotic tissue, 18F-fluoride bound avidly to regions of cerebral infarction (SUVmean 4.8±1.98 versus SUVmean of 0.07±0.02, infarcted versus non-infarcted cerebrum; p<0.001). Carotid 18F-FDG uptake appeared to be increased in 7/16 culprit plaques but no overall differences in uptake were observed in the culprit versus the contralateral plaques or control patients. However, 18F-FDG did correlate with predicted cardiovascular risk (r=0.53, p=0.019) but not with plaque phenotype. Conclusion: 18F-Fluoride PET/CT highlights culprit carotid plaque. This has the potential to improve risk-stratification and the selection of those patients who would benefit from surgical intervention.